2018
DOI: 10.1002/jhet.3356
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis and Spectral Characterization of Biological Activity Heterocyclic Thiosemicarbazone and Its Organometallic Derivatives

Abstract: The thiosemicarbazone coordinates to metal through the thionic sulfur and the azomethine nitrogen. The thiosemicarbazone was obtained by the thiosemicarbazide with 3‐acetyl‐2,5‐dimethylfuran by microwave irradiation. Metal complexes were prepared by the reaction of thiosemicarbazone with metal salts. IR, 1H, 13C NMR, FAB‐mass spectroscopic methods, and elemental analysis elucidated the structure of these compounds. The antibacterial activity of these compounds were first tested in vitro by the disk diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…These functional groups were initially studied as anti-tuberculosis agents, [22] but over time it was found that they represent privileged motives in medicinal chemistry, exhibiting an extensive range of biological activities, including antifungal, antitumor, hypnotic, antiviral and antimalarial effects. [23][24][25][26] Additionally, due to the presence of lone pair electrons in the nitrogen and the sulfur atoms, TSC can serve as versatile ligands with a broad variety of coordination modes, exerting an important role in biological processes. [27] The first clinically approved drug of this compound class is Thioacetazone (Figure 1), [24,28] which has been wildly used in the past as a companion drug, together with first-line TB medications.…”
Section: Introductionmentioning
confidence: 99%
“…These functional groups were initially studied as anti-tuberculosis agents, [22] but over time it was found that they represent privileged motives in medicinal chemistry, exhibiting an extensive range of biological activities, including antifungal, antitumor, hypnotic, antiviral and antimalarial effects. [23][24][25][26] Additionally, due to the presence of lone pair electrons in the nitrogen and the sulfur atoms, TSC can serve as versatile ligands with a broad variety of coordination modes, exerting an important role in biological processes. [27] The first clinically approved drug of this compound class is Thioacetazone (Figure 1), [24,28] which has been wildly used in the past as a companion drug, together with first-line TB medications.…”
Section: Introductionmentioning
confidence: 99%